Autism and ADHD: A Literature Review Regarding Their Impacts on Parental Divorce - Smeralda Diandra Anchesi; Francesco Corallo; Marcella Di Cara; Angelo Quartarone; Rino Catalioto; Francesca Cucinotta; Davide Cardile (MDPI AG, 2023)
Introduction: The change in family structure as a consequence of divorce can be a traumatic event for a child that can undermine his or her emotional security. For this reason, it becomes a major health concern. Many divorce-related risk factors have been identified, including attention deficits or autism spectrum disorder (ASD) in children. The aim of this review is to evaluate if and how a diagnosis of ASD or attention deficit hyperactivity disorder (ADHD) in children is associated with an increase in divorce within families. Method: Searches were performed in two databases evaluating studies focusing on articles pertaining to the topic. A total of 20 articles were found, but only 8 were included in the study according to the criteria. Results: The results showed that divorce does not appear to be specifically related to a diagnosed pathology of the child, but rather presents itself as a risk factor in certain situations. In particular, this occurs when the coping strategies required to deal with the diagnosis are dysfunctional. However, it would appear that families in which there are children with ADHD have a greater chance of divorce than families in which there is a child with a diagnosis of ASD. It may be hypothesised that in the latter case, parents receiving a diagnosis early in the child's life have more time to develop adaptive strategies to cope with the condition than parents with children with ADHD who mostly find themselves having to deal with their child's behavioural problems at a school age. Moreover, ASD is a disorder more likely genetic than environment-related, so parents receive more socio-medical support, and they are less likely to blame themselves or be blamed by others.